Flödeslarm 112 : Gränssnitt för gasövervakning i vägambulans - Björnfot Nilsson, Anna (2014)
This dissertation represents a master thesis in the education Industrial design engineering for a master of science degree in in Product design, at Luleå University of Technology. The objective of the assignment was to create a user interface design concept for a gas alarm, to be used in respiratory care with medical air and oxygen during ambulance transport. The educational objective was to select, apply, and immerse theories and practices relevant to the product subject and the assignment statement. The assignment was provided by Länsteknik Medical Technology in Luleå, Norrbotten. Most of the thesis assignment-related part has been carried out for the ambulance service in Luleå, after that, in consultation with Länsteknik, it was decided that the gas alarm would be developed with a focus on users in integration with the user environment.The project originated from paramedics’ complaints about the lack of easy monitoring of the flow of gas from the air and oxygen bottles. That means problems when they do not discover until afterwards if treatments are not continued, because the gas bottle is empty or incorrectly installed. Upon closer inspection of the situation it was found that there is also need for a reminder to shut off gas flow, as this is another procedure that paramedics might otherwise oversee. Hence the first task was to establish if there really is a need for a gas flow alarm and why. Further the study has been about designing proposals for a suitable gas alarm which is to sense and notify if the bottle is open, closed or when the bottle is empty.In order to provide appropriate boisterous it is needed to send out matching signals about what will be alerted. Development has taken place from two different perspectives. First a wider where the studies focused on identifying what kind of signals that are suitable for alarm presentation and for what purposes. Subsequently, a more narrow perspective in which it was determined what kind of signals that would be used, and the work was concentrated on the ...